DETERMINAN PENCEGAHAN FRAUD PADA PENGELOLAAN DANA DESA DENGAN MORALITAS SEBAGAI MODERASI: DETERMINANTS OF FRAUD PREVENTION IN VILLAGE FUND MANAGEMENT WITH MORALITY AS MODERATION - Muslim, Ego; Taufik, Taufeni; Azlina, Nur (Universitas Riau, 2025)
This study aims to analyze the influence of apparatus competence, internal control systems, and whistleblowing systems on fraud prevention in village fund management, with morality as a moderating variable, within the village governments of Kampar Regency. Employing a quantitative approach, the study collected primary data through questionnaires. The population comprised all 242 villages in Kampar Regency, and the sampling technique used was a census (saturation) method. A total of 726 respondents were selected based on predetermined criteria. Data processing was performed using SPSS version 27, and Moderated Regression Analysis (MRA) with interaction tests was applied for data analysis. The results indicates that apparatus competence and internal control systems have a significant effect on fraud prevention in village fund management, whereas the whistleblowing system does not show a significant effect. Furthermore, morality moderates the influence of apparatus competence, internal control systems, and whistleblowing systems on fraud prevention. These findings provide practical guidance for village governments to enhance training, transparency, and ethical culture, thereby minimizing the risk of fraud. The implementation of these measures is expected to foster more accountable and integrated governance of village funds.